Preparation method and application of carbon-coated lithium sulfide hollow sphere positive electrode material
The carbon-coated lithium sulfide hollow ball cathode material is prepared by spray drying and carbon thermal reduction reaction, which solves the problems of high cost and poor conductivity of commercial lithium sulfide materials, and achieves the effect of improving conductivity and electrochemical activity.
Patent Information
- Application Number
- CN202211417773.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-14
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-11-14
AI Technical Summary
Commercial lithium sulfide materials have high cost, poor conductivity and poor electrochemical activity, which limit their application in lithium secondary batteries.
The carbon-coated lithium sulfide hollow ball positive electrode material is prepared by spray drying and carbon thermal reduction, thereby improving the conductivity and electrochemical activity of the lithium sulfide material.
The manufacturing cost of lithium sulfide positive electrode material is reduced, the conductivity and electrochemical activity are improved, and the active specific surface area of the positive electrode material is increased.
Smart Images

Figure CN115714169B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new energy technology and relates to a preparation method and application of a carbon-coated lithium sulfide hollow sphere positive electrode material. Background Art
[0002] Traditional lithium-ion batteries are widely used in electronic devices and electric vehicle industries, but their low energy density can no longer meet the growing energy demand in emerging fields. Therefore, it is urgent to design and develop a new type of secondary battery with higher energy density and longer cycle life.
[0003] Electrode materials are the core components of battery systems and the key bottleneck restricting the improvement of battery energy density. Lithium sulfide is an emerging secondary battery electrode material with many advantages. First, its theoretical specific capacity (1166mA hg -1 ) is more than three times that of traditional oxide electrodes. Secondly, the high melting point characteristic (938°C) makes it adaptable to a variety of rigorous electrode preparation methods. Finally, as a fully lithiated state of sulfur, it can be matched with a variety of lithium storage negative electrodes that do not contain metallic lithium, avoiding the safety risks caused by metallic lithium. However, commercial lithium sulfide materials have problems such as high price, poor conductivity, poor electrochemical activity, and polysulfide dissolution and shuttling, which limit their application in lithium secondary batteries. Summary of the invention
[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing a carbon-coated lithium sulfide hollow sphere positive electrode material. Carbon-coated lithium sulfide hollow spheres are prepared by a two-step reaction of spray drying and carbon thermal reduction. The lithium sulfide positive electrode material prepared by this method improves the problems of high cost, poor conductivity and poor electrochemical activity of commercial lithium sulfide, and achieves the purpose of improving the utilization rate of active substances in the positive electrode material.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for preparing a carbon-coated lithium sulfide hollow sphere positive electrode material. Lithium sulfate is spray-dried to form lithium sulfate hollow spheres, which are mixed with a carbon source precursor and then carbon-thermal reduction is used to prepare carbon-coated lithium sulfide hollow spheres. The spray-drying process is a pressure spray or ultrasonic spray process; and the carbon source precursor is at least one of polyvinyl pyrrolidone, polyethylene glycol, and fructose.
[0007] A method for preparing a carbon-coated lithium sulfide hollow sphere positive electrode material specifically comprises the following steps:
[0008] 1) Dissolve lithium sulfate in deionized water at room temperature and pressure to form a homogeneous solution with a concentration of 10-40 mg / mL -1 .
[0009] 2) spray drying the solution with a pressure spray dryer to obtain lithium sulfate hollow sphere powder. The fan frequency of the spray dryer is 100%, the air inlet temperature is 140-220°C, and the peristaltic pump feed rate is 10-20r / min;
[0010] 3) Or use an ultrasonic spray dryer to atomize the solution to obtain lithium sulfate aerosol droplets, use an inert gas as a carrier gas, blow the aerosol droplets into a high-temperature furnace at a preset temperature, and quickly dry to obtain lithium sulfate hollow sphere powder. The preset temperature of the high-temperature furnace is 400-800°C, the inert gas is at least one of nitrogen, argon or helium, and the carrier gas flow rate is 0.1-1.0L h -1 .
[0011] 4) Dissolve cobalt acetate and carbon source precursor in anhydrous ethanol, stir for 4-8 hours in an oil bath at 60-80°C to obtain a carbon source precursor solution. The carbon source precursor is at least one of polyvinyl pyrrolidone, polyethylene glycol, and fructose; the concentration of cobalt acetate is 0.01-0.02 mol L -1 ; The content of the carbon source precursor is 30-45mg mL -1 .
[0012] 5) Add the lithium sulfate hollow sphere powder prepared in step 2) or step 3) to the carbon source precursor solution prepared in step 4), fully dry to remove the solvent, and heat treat in air atmosphere to obtain brown powder. The heat treatment temperature is 260-280°C and the heat treatment time is 2-3h. The mass ratio of lithium sulfate hollow spheres to carbon source precursor in the dispersion is 1:1.2-1:1.5, and the concentration of lithium sulfate hollow spheres is 20-30mg mL -1 .
[0013] 6) The brown powder prepared in step 5) is subjected to high-temperature carbonization treatment in an inert atmosphere to obtain a carbon-coated lithium sulfide hollow sphere material. The carbonization temperature is 750-850°C and the carbonization time is 2-3h. The main chemical reactions in the carbonization process are: The lithium sulfide loading in the obtained composite material is 60-80wt.%, the cobalt single substance loading is 5-10wt.%, and the inert gas is at least one of nitrogen, argon or helium.
[0014] The carbon-coated lithium sulfide hollow sphere positive electrode material prepared by the above method is applied to lithium secondary batteries, especially lithium sulfide batteries.
[0015] Compared with the prior art, the present invention solves the application problem of commercial lithium sulfide materials, and its beneficial effects are:
[0016] (1) The lithium sulfide / carbon composite material is synthesized by cheap lithium sulfate and carbon source, which greatly reduces the manufacturing cost of lithium sulfide positive electrode materials and the process is simple and easy.
[0017] (2) The hollow structure of lithium sulfide / carbon composite positive electrode materials can effectively improve the conductivity of lithium sulfide and increase the active specific surface area of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a scanning electron microscope photograph of the lithium sulfate hollow spheres prepared in Example 1 of the present invention;
[0019] Figure 2 is a scanning electron microscope photograph of the lithium sulfate hollow spheres prepared in Example 2 of the present invention;
[0020] Figure 3 is a scanning electron microscope photograph of the carbon-coated lithium sulfide hollow sphere positive electrode material prepared in Example 3 of the present invention;
[0021] Figure 4 1 is the voltage capacity curve of the carbon-coated lithium sulfide hollow sphere positive electrode material prepared in Example 4 of the present invention;
[0022] Figure 5 The coulombic efficiency and cycle stability of the carbon-coated lithium sulfide hollow sphere positive electrode material prepared in Example 5 of the present invention;
[0023] Figure 6 This is the rate performance of the carbon-coated lithium sulfide hollow sphere positive electrode material prepared in Example 6 of the present invention. DETAILED DESCRIPTION
[0024] In view of the many defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle, etc. will be further explained as follows. However, it should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described in the following (embodiments) can be combined with each other to form a new or preferred technical solution.
[0025] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0026] Example 1
[0027] 1) Dissolve lithium sulfate in deionized water at room temperature and pressure to form a homogeneous solution with a concentration of 20 mg mL -1 .
[0028] 2) Using a pressure spray dryer to spray dry the solution to obtain lithium sulfate hollow sphere powder, wherein the fan frequency of the spray dryer is 100%, the air inlet temperature is 180° C., and the peristaltic pump feed rate is 10 r / min.
[0029] 3) Dissolve cobalt acetate and carbon source precursor in anhydrous ethanol, stir for 6 hours in an oil bath at 75°C to obtain a carbon source precursor solution. The carbon source precursor is polyvinyl pyrrolidone; the concentration of cobalt acetate is 0.02 mol L -1 ; The content of the carbon source precursor is 45mg mL -1 .
[0030] 4) Add the lithium sulfate hollow sphere powder prepared in step 2) to the carbon source precursor solution prepared in step 3), fully dry to remove the solvent, and heat treat in air atmosphere to obtain brown powder. The heat treatment temperature is 270°C and the heat treatment time is 2h. The mass ratio of lithium sulfate hollow spheres to carbon source precursor in the dispersion is 1:1.5, and the concentration of lithium sulfate hollow spheres is 30mg mL -1 .
[0031] 5) The brown powder prepared in step 4) is subjected to high-temperature carbonization treatment in an inert atmosphere to obtain a carbon-coated lithium sulfide hollow sphere material. The carbonization temperature is 800° C. and the carbonization time is 2 hours. The lithium sulfide loading in the obtained composite material is 60 wt.%, and the cobalt loading is 6 wt.%, and the inert gas is argon.
[0032] like Figure 1 As shown, the lithium sulfate hollow spheres prepared by the spray drying method have good sphericity and the particle size of the spheres is 1 to 4 μm.
[0033] Example 2
[0034] 1) Dissolve lithium sulfate in deionized water at room temperature and pressure to form a homogeneous solution with a concentration of 10 mg mL -1 .
[0035] 2) The solution is spray-dried by a pressure spray dryer to obtain lithium sulfate hollow sphere powder, wherein the fan frequency of the spray dryer is 100%, the air inlet temperature is 220° C., and the peristaltic pump feed rate is 15 r / min.
[0036] 3) Dissolve cobalt acetate and carbon source precursor in anhydrous ethanol, stir for 8 hours in an oil bath at 70°C to obtain a carbon source precursor solution. The carbon source precursor is polyethylene glycol; the concentration of cobalt acetate is 0.01 mol L -1 ; The content of the carbon source precursor is 30mg mL -1 .
[0037] 4) Add the lithium sulfate hollow sphere powder prepared in step 2) to the carbon source precursor solution prepared in step 3), fully dry to remove the solvent, and heat treat in air atmosphere to obtain brown powder. The heat treatment temperature is 280°C and the heat treatment time is 2h. The mass ratio of lithium sulfate hollow spheres to carbon source precursor in the dispersion is 1:1.2, and the concentration of lithium sulfate hollow spheres is 20mg mL -1 .
[0038] 5) The brown powder prepared in step 4) is subjected to high-temperature carbonization treatment in an inert atmosphere to obtain a carbon-coated lithium sulfide hollow sphere material. The carbonization temperature is 850° C. and the carbonization time is 2 hours. The lithium sulfide loading in the obtained composite material is 80 wt.%, and the cobalt loading is 5 wt.%, and the inert gas is helium.
[0039] like Figure 2 As shown, the hollow spheres prepared by spray drying are composed of lithium sulfate monoclinic crystals with a relatively smooth surface.
[0040] Example 3
[0041] 1) Dissolve lithium sulfate in deionized water at room temperature and pressure to form a homogeneous solution with a concentration of 40 mg mL -1 .
[0042] 2) The solution is spray-dried by a pressure spray dryer to obtain lithium sulfate hollow sphere powder, wherein the fan frequency of the spray dryer is 100%, the air inlet temperature is 140° C., and the peristaltic pump feed rate is 20 r / min.
[0043] 3) Dissolve cobalt acetate and carbon source precursor in anhydrous ethanol, stir for 4 hours in an 80°C oil bath to obtain a carbon source precursor solution. The carbon source precursor is fructose; the concentration of cobalt acetate is 0.02 mol L -1 ; The content of the carbon source precursor is 40mg mL -1 .
[0044] 4) Add the lithium sulfate hollow sphere powder prepared in step 2) to the carbon source precursor solution prepared in step 3), fully dry to remove the solvent, and heat treat in air atmosphere to obtain brown powder. The heat treatment temperature is 260°C and the heat treatment time is 3h. The mass ratio of lithium sulfate hollow spheres to carbon source precursor in the dispersion is 1:1.5, and the concentration of lithium sulfate hollow spheres is 30mg mL -1 .
[0045] 5) The brown powder prepared in step 4) is subjected to high-temperature carbonization treatment in an inert atmosphere to obtain a carbon-coated lithium sulfide hollow sphere material. The carbonization temperature is 750° C. and the carbonization time is 3 hours. The lithium sulfide loading in the obtained composite material is 60 wt.%, and the cobalt loading is 10 wt.%, and the inert gas is nitrogen.
[0046] like Figure 3 As shown, in the prepared carbon-coated lithium sulfide hollow sphere positive electrode material, the lithium sulfide spheres are uniformly coated with a carbon layer, and the three-dimensional structure is conducive to the efficient transfer of charges and materials during the electrochemical cycle process.
[0047] Example 4
[0048] 1) Dissolve lithium sulfate in deionized water at room temperature and pressure to form a homogeneous solution with a concentration of 20 mg mL -1 .
[0049] 2) Using an ultrasonic spray dryer to atomize the solution to obtain lithium sulfate aerosol droplets, using an inert gas as a carrier gas, the aerosol droplets are blown into a high-temperature furnace at a preset temperature, and after rapid drying, lithium sulfate hollow sphere powder is obtained. The preset temperature of the high-temperature furnace is 600°C, the inert gas is argon, and the carrier gas flow rate is 0.1 L h -1 .
[0050] 3) Dissolve cobalt acetate and carbon source precursor in anhydrous ethanol, stir for 4 hours in an oil bath at 60°C to obtain a carbon source precursor solution. The carbon source precursor is fructose; the concentration of cobalt acetate is 0.02 mol L -1 ; The content of the carbon source precursor is 45mg mL -1 .
[0051] 4) Add the lithium sulfate hollow sphere powder prepared in step 2) to the carbon source precursor solution prepared in step 3), fully dry to remove the solvent, and heat treat in air atmosphere to obtain brown powder. The heat treatment temperature is 270°C and the heat treatment time is 2.5h. The mass ratio of lithium sulfate hollow spheres to carbon source precursor in the dispersion is 1:1.4, and the concentration of lithium sulfate hollow spheres is 30mg mL -1 .
[0052] 5) The brown powder prepared in step 4) is subjected to high-temperature carbonization treatment in an inert atmosphere to obtain a carbon-coated lithium sulfide hollow sphere material. The carbonization temperature is 800° C. and the carbonization time is 2.5 h. The lithium sulfide loading in the obtained composite material is 65 wt.%, and the cobalt loading is 6 wt.%, and the inert gas is nitrogen.
[0053] like Figure 4As shown, the capacity-voltage curve of the prepared carbon-coated lithium sulfide hollow sphere positive electrode material at a rate of 0.2C. The discharge capacity reached 640.2 mA hg -1 .
[0054] Example 5
[0055] 1) Dissolve lithium sulfate in deionized water at room temperature and pressure to form a homogeneous solution with a concentration of 30 mg mL -1 .
[0056] 2) Using an ultrasonic spray dryer to atomize the solution to obtain lithium sulfate aerosol droplets, using an inert gas as a carrier gas, the aerosol droplets are blown into a high-temperature furnace at a preset temperature, and after rapid drying, lithium sulfate hollow sphere powder is obtained. The preset temperature of the high-temperature furnace is 800°C, the inert gas is helium, and the carrier gas flow rate is 1 L h -1 .
[0057] 3) Dissolve cobalt acetate and carbon source precursor in anhydrous ethanol, stir for 6 hours in an oil bath at 70°C to obtain a carbon source precursor solution. The carbon source precursor is polyvinyl pyrrolidone; the concentration of cobalt acetate is 0.01 mol L -1 ; The content of the carbon source precursor is 30mg mL -1 .
[0058] 4) Add the lithium sulfate hollow sphere powder prepared in step 2) to the carbon source precursor solution prepared in step 3), fully dry to remove the solvent, and heat treat in air atmosphere to obtain brown powder. The heat treatment temperature is 280°C and the heat treatment time is 2h. The mass ratio of lithium sulfate hollow spheres to carbon source precursor in the dispersion is 1:1.5, and the concentration of lithium sulfate hollow spheres is 20mg mL -1 .
[0059] 5) The brown powder prepared in step 4) is subjected to high-temperature carbonization treatment in an inert atmosphere to obtain a carbon-coated lithium sulfide hollow sphere material. The carbonization temperature is 780° C. and the carbonization time is 2 hours. The lithium sulfide loading in the obtained composite material is 60 wt.%, and the cobalt loading is 5 wt.%, and the inert gas is argon.
[0060] like Figure 5 The figure shows the coulombic efficiency and cycle stability of the carbon-coated lithium sulfide hollow sphere positive electrode material. It can be stably cycled for 100 cycles at 0.2C, showing good cycle stability.
[0061] Example 6
[0062] 1) Dissolve lithium sulfate in deionized water at room temperature and pressure to form a homogeneous solution with a concentration of 20 mg mL -1 .
[0063] 2) Using an ultrasonic spray dryer to atomize the solution to obtain lithium sulfate aerosol droplets, using an inert gas as a carrier gas, the aerosol droplets are blown into a high-temperature furnace at a preset temperature, and after rapid drying, lithium sulfate hollow sphere powder is obtained. The preset temperature of the high-temperature furnace is 650°C, the inert gas is nitrogen, and the carrier gas flow rate is 0.5 L h -1 .
[0064] 3) Dissolve cobalt acetate and carbon source precursor in anhydrous ethanol, stir for 8 hours in an oil bath at 80°C to obtain a carbon source precursor solution. The carbon source precursor is polyvinyl pyrrolidone; the concentration of cobalt acetate is 0.015 mol L -1 ; The content of the carbon source precursor is 35mg mL -1 .
[0065] 4) Add the lithium sulfate hollow sphere powder prepared in step 2) to the carbon source precursor solution prepared in step 3), fully dry to remove the solvent, and heat treat in air atmosphere to obtain brown powder. The heat treatment temperature is 270°C and the heat treatment time is 2h. The mass ratio of lithium sulfate hollow spheres to carbon source precursor in the dispersion is 1:1.4, and the concentration of lithium sulfate hollow spheres is 25mg mL -1 .
[0066] 5) The brown powder prepared in step 4) is subjected to high-temperature carbonization treatment in an inert atmosphere to obtain a carbon-coated lithium sulfide hollow sphere material. The carbonization temperature is 800° C. and the carbonization time is 2 hours. The lithium sulfide loading in the obtained composite material is 65wt.%, and the cobalt loading is 6wt.%, and the inert gas is argon.
[0067] like Figure 6 As shown in the figure, the rate performance of the carbon-coated lithium sulfide hollow sphere positive electrode material is -1 ) current density, there is still 319.5mA hg -1 When the current returns to 0.1C (1C = 1166mA g -1 ) the discharge capacity can be restored to 543.6 mA hg -1 .
[0068] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the scope of protection of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the scope of protection of the present invention. Although the above describes the specific implementation mode of the present invention in conjunction with the accompanying drawings, it is not a limitation on the scope of protection of the present invention. Those skilled in the art should understand that on the basis of the technical solution of the present invention, various modifications or deformations that can be made by those skilled in the art without creative labor are still within the scope of protection of the present invention.
Claims
1. A method for preparing a carbon-coated lithium sulfide hollow sphere positive electrode material, characterized in that: Lithium sulfate is spray-dried to form lithium sulfate hollow spheres, which are mixed with a carbon source precursor and then carbon-coated lithium sulfide hollow spheres are prepared by carbothermal reduction reaction; wherein the spray-drying process is a pressure spray or ultrasonic spray process; specifically, the following steps are included: 1) dissolving lithium sulfate in deionized water at room temperature and pressure to form a homogeneous solution; 2) spray drying the solution with a pressure spray dryer to obtain lithium sulfate hollow sphere powder; or atomizing the solution with an ultrasonic spray dryer to obtain lithium sulfate aerosol droplets, using an inert gas as a carrier gas, blowing the aerosol droplets into a high-temperature furnace at a preset temperature, and obtaining lithium sulfate hollow sphere powder after rapid drying; 3) dissolving cobalt acetate and carbon source precursor in anhydrous ethanol, stirring for 4-8 hours in an oil bath at 60-80° C., to obtain a carbon source precursor solution; 4) adding the lithium sulfate hollow sphere powder prepared in step 2) to the carbon source precursor solution prepared in step 3), fully drying to remove the solvent, and heat treating in an air atmosphere to obtain a brown powder; wherein the heat treatment temperature is 260-280° C., and the heat treatment time is 2-3 h; 5) The brown powder prepared in step 4) is subjected to high-temperature carbonization treatment in an inert atmosphere to obtain a carbon-coated lithium sulfide hollow sphere material; wherein the carbonization temperature is 750-850° C.; the carbonization time is 2-3 h; the lithium sulfide loading in the obtained composite material is 60-80 wt.%, and the cobalt loading is 5-10 wt.%.
2. The method for preparing a carbon-coated lithium sulfide hollow sphere positive electrode material according to claim 1, characterized in that: In step 1), the concentration of the homogeneous solution is 10-40 mg mL -1 .
3. The method for preparing a carbon-coated lithium sulfide hollow sphere positive electrode material according to claim 1, characterized in that: In the step 2), the fan frequency of the spray dryer is 100%, the air inlet temperature is 140-220° C., and the peristaltic pump feed rate is 10-20 r / min.
4. The method for preparing a carbon-coated lithium sulfide hollow sphere positive electrode material according to claim 1, characterized in that: In step 2), the preset temperature of the high temperature furnace is 400-800°C, the inert gas is at least one of nitrogen, argon or helium, and the carrier gas flow rate is 0.1-1.0 L h -1 .
5. The method for preparing a carbon-coated lithium sulfide hollow sphere positive electrode material according to claim 1, characterized in that: In step 3), the carbon source precursor is at least one of polyvinyl pyrrolidone, polyethylene glycol, and fructose; the concentration of cobalt acetate is 0.01-0.02 mol L -1 ; The content of the carbon source precursor is 30-45mg mL -1 .
6. The method for preparing a carbon-coated lithium sulfide hollow sphere positive electrode material according to claim 1, characterized in that: In the step 4), the mass ratio of the lithium sulfate hollow sphere to the carbon source precursor is 1:1.2-1:1.5, and the concentration of the lithium sulfate hollow sphere is 20-30 mg mL -1 .
7. An application of a carbon-coated lithium sulfide hollow sphere positive electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6 and is applied to lithium secondary batteries.
Citation Information
Patent Citations
Preparation method of easy-to-activate high-carrying-capacity lithium sulfide carbon composite material and application of preparation method
CN110112390A
Lithium-sulfur battery cathode material and preparation method thereof
CN111900407A
Cited By
Lithium sulfide composite positive electrode material with difunctional network structure as well as preparation method and application of lithium sulfide composite positive electrode material
CN121546045A